Synergic modulation of over-stoichiometrical MnO2 and SiO2-coated particles on the energy storage properties of silver niobate-based ceramics. Issue 14 (15th July 2021) - Wang, Jing; Rao, Yu; Fan, Xuhui; Zhang, Jin; Zhao, Lei; Zhu, Kongjun
Abstract: AgNbO3 -based ceramics have been the spotlight for the lead-free dielectric capacitors due to its unique antiferroelectric feature and the ever-increasing environmental concerns. Herein, synergic modulation on the energy storage properties of AgNbO3 -based ceramics was reported, in which the over-stoichiometrical introduction of only 0.10 wt% MnO2 at the atomic-scale leads to reduced leakage current, P r and enhanced antiferroelectric stability while the SiO2 coating on the AgNbO3 particles at the micro-scale greatly inhibits the grain growth, increases the breakdown strength and the electric filed inducing the AFE-FE transitions. As a result, a large recoverable energy density up to 3.34 J/cm 3 with efficiency of 60.0% was obtained in 0.10 wt% MnO2 -doped AgNbO3 @SiO2 ceramic, which is 2.3 times larger than that of the pristine AgNbO3 . This work provides a rational approach to synergically modulate the energy storage properties.